Static voltage balance method of CDSM‐MMC based on power supply control. Issue 2 (1st February 2020) - Yang, Lixia; Jia, Lixin; Luo, Longfei; Zhang, Yanbin; Si, Gangquan; Zhang, Zhuxiang
Abstract : Recently, the clamp double sub‐module (CDSM) topology with its DC fault clearance ability has become more attractive for use in the modular multilevel converter (MMC)‐based high‐voltage DC transmission systems. However, the capacitor voltage imbalance caused by the discreteness of the device parameters during the uncontrolled pre‐charging process seriously affects the system's safe start‐up. To solve this problem, this study provides a novel CDSM‐MMC capacitor static voltage balance method. Since the power supplies obtaining energy from the CDSM capacitors greatly influence the static voltage balance, the power supply input current is chosen as the control variable. On the basis of the control signals generated by the voltage balance algorithm, the control of the CDSM power supply input currents makes the arm energy be an average distribution in the CDSM capacitors. This method can replace the capacitor equalising resistors of CDSM to achieve capacitor voltage balance and can reduce the CDSM‐MMC's losses. The method requires no additional circuits, and the control strategy is simple. Moreover, the method can apply to the static voltage balance control of other SM topologies with two capacitors. An arm cascaded with two CDSMs is tested and the results show the effectiveness of the proposed method.